Uji Kualitas Bakteri pada Terasi Toboali dengan Lama Fermentasi yang Berbeda - Henny Helmi; Ahmad Arsyadi; Salmi Salmi (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
Terasi is a condiment in a variety of Indonesian cuisine. Toboali’s shrimp paste is made in the Toboali district, South Bangka. This shrimp paste is famous for being delicious and without other additives such as preservatives and coloring agent. The purpose of this study was to compare the bacteria quality of shrimp paste with different fermentation times. The salt content used in this study was 20%. Shrimp used as raw material in this study was A. japonicus and the salt used was solar salt. The results showed that the shrimp paste at 0 and 7 days of fermentation contained coliform and colifecal. After 14 days and 28 days of fermentation, the shrimp paste did not contain coliform and colifecal. All samples did not contain E.coli and Salmonella. Meanwhile, the total nonhalophilic bacteria and halophilic bacteria decreased until the end of fermentation. Lactic acid bacteria increased until 14 days fermentation and decreased until the end of fermentation. Non-halophilic bacteria was still above the permissible number for food product safety (more than 105 CFU/g) up to 21 days of fermentation. Based on the results obtained, the shrimp paste should be fermented up to 28 days of fermentation to reduce the number of coliform, colifecal and total non-halophilic bacteria.